"Modelamiento matemático para el generador de inducción doblemente alimentado trabajando con saturación en sistemas de generación eólica." - Arroyo Quintero, Liliana Janeth (2019)
The present research project exhibits significant aspects of the new technologies used for the production of renewable energy based on wind, without a doubt there have been great changes applied to this form of energy production in recent years, allowing some way move or replace those expensive and environmentally friendly generation systems. Basically the purpose of this research is to expose the reader the characteristics of a wind generation system with DFIG, as well as the importance of incorporating the magnetic saturation that usually occurs in this type of generators, to determine the real behavior of these, Since under normal or nominal conditions these machines operate without saturation, however, under certain operating conditions, considering the model as linear is not adequate. For the study, the model developed in [1] was taken with which we worked on the analysis of the effects caused in the machine due to the incorporation of saturation, as well as the effects before the appearance of voltage gaps, surges and the variations in behavior when it operates with and without saturation, these conditions accompanied by simulation techniques in Matlab / simulink will contribute to obtaining a more strict model that represents the correct operation of the machine under certain conditions; For this purpose, the identification of non-linear systems will be used as a method to obtain the mathematical model that allows to represent the behavior of the system.